Successful use of trastuzumab deruxtecan in hepatic visceral crisis secondary to metastatic HER2-low breast cancer - Kapoor, Nilesh; Su, Malcolm; Horadam, Rochelle; Klemow, Dawn; Syed, Samira (Current problems in cancer. Case reports, 2025)
•Up to 20 % of patients with metastatic breast cancer develop hepatic visceral crisis, a life-threatening condition that implies impending liver failure and death.•Combination chemotherapy is recommended for hepatic visceral crisis however the outcomes are generally dismal.•Trastuzumab deruxtecan is a recently approved antibody-drug conjugate with high response rates in metastatic HER2-positive, HER2-low, and HER2-ultralow breast cancers.•No guidelines on administration or dose adjustment for trastuzumab deruxtecan are available for severe hepatic impairment.•This case study shows that trastuzumab deruxtecan can be effective in hepatic visceral crisis and further studies should validate its use in this setting. Hepatic visceral crisis is a life-threatening manifestation of disease progression in 10–20 % of patients with metastatic breast cancer. The condition is defined as a rapid rise in bilirubin > 1.5 times upper limit of normal (ULN) in the absence of biliary tract obstruction or Gilbert’s syndrome. Prompt disease control is required to prevent progression to liver failure and death. There are no standard treatment regimens for hepatic visceral crisis and the prognosis is dismal. Trastuzumab deruxtecan (T-DXd) is an antibody-drug conjugate that has recently been approved for patients with metastatic HER2-positive, HER2-low, and HER2-ultralow breast cancer after progression on prior chemotherapy or endocrine therapy. Patients with hepatic visceral crises were not included in any clinical trials for T-DXd and, therefore, no manufacturer-based guidelines on administration or dosing of T-DXd are available in this setting. In this case study, a patient with metastatic HER2-low breast cancer presented with hepatic visceral crisis after progression on two prior lines of endocrine-based therapy. Within a span of days, her total bilirubin had risen to 19 mg/dL and her AST and ALT were both > 15 times ULN. She was offered T-DXd and had rapid, dramatic improvement in her liver chemistries and in her functional status. She received the drug for 25 cycles, resulting in a durable clinical and radiographic response for one and a half years. This case study supports the use of T-DXd in hepatic visceral crisis. Further research should be done to validate its use in this life-threatening setting.